Perbandingan Model Pembelajaran Kooperatif Tipe Scramble Berbantuan Media Papan Baca Pintar terhadap Kemampuan Membaca Permulaan - Dewi Handayani; Kadek Dewi Wahyuni Andari; Agustinus Toding Bua (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
This study aims to determine differences in students' initial reading skills by applying the Sramble learning model assisted by the Smart Reading Board Media with the institution's word method in class I SD Muhammadiyah 2 Tarakan. This type of research is quasi-experimental research. This research was conducted in May 2019. With a population of students in grade I of SD Muhammadiyah 2 Tarakan and the sample consisted of two classes, namely class I (Al-Furqon) as an experimental class and class I (Al-Fatihah) as a control class. The technique in taking the sample used is Random Sampling. The research data were processed with the help of SPSS V.21 for Windows Software. The results showed that there were no differences in the results of initial reading ability by applying the Scramble Type Cooperative Learning Model aided by the Smart Reading Board Media with the Institution Word Method. The results of the Independent Sample T-test on students' initial reading ability were obtained tcount = 0,037 at the 0,05 significance level and df = 53, obtained ttable = 2,01 means tcount ? ttable. This it can be concluded that there is no difference in the ability to read the beginning of students by applying the Sramble learning model assisted by the Smart Reading Board Media with the Institution Word Method in Grade I students of SD Muhammadiyah 2 Tarakan.